Utilizing Cooperative Learning Model Types Make a Match to Promote Primary Students’ Achivement in Science - N, Lazim; Aldriyanti, Novi; Alpusari, Mahmud; Hermita, Neni; Mahbubah, Khoiro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study aims to promote primary students’ achivement in scince learning utilizing cooperative leraning model types make a match. The method is Classroom Action Research by applying cooperative learning model type make a match. The data collected in this research are observation sheet of teacher activity and student activity and learning result. The average learning outcomes of science obtained before the action was 62.33 increased to 77.67 in first cycle by percentage of 24.61%. In the second cycle increased to 88.00 with a percentage increase of 41.18%. Thus, it can beconcluded that cooperative learning model type make a match efeectively to promote primary students’ achivement in science learning.